Kajian Yuridis Tindak Pidana Penipuan Pemberangkatan Haji dan Umrah - Abdul Rahman Anwar; Muh. Fadli Faisal Rasyid; Muh. Akbar Fhad Syahril (Jurnal Litigasi Amsir, 2023)
This study aims to determine the factors that cause the occurrence of criminal acts of fraud with the mode of departure for Hajj and Umrah in the city of Parepare. And to find out the legal considerations by the judges in deciding cases of criminal acts of fraud against Hajj and Umrah departures in the city of Parepare based on the MA Decision Study Number 1163 K/Pid/2021 whether or not they are in accordance with alternative charges. The type of research used in this study is normative and empirical legal research. Supported by a research approach, namely the sociological juridical approach and the case approach. The results showed that the factors that caused the crime of fraud with the Haj and Umrah departure mode in the city of Parepare were the character of people who easily believed, lack of understanding regarding the official nature of travel, the desire of people who wanted to quickly go on pilgrimage and umrah, not being careful. the public is careful or less alert, the way travel agents attract public interest and trust, and a lack of counseling regarding the departure of the Hajj and Umrah pilgrimages. Second, legal considerations by judges pay attention to several aspects apart from the legal facts that have occurred, also related to alternative charges. Even though there were two alternative charges, namely Article 378 concerning Fraud and Article 372 of Embezzlement, in the end the judge determined that the defendant H. Abdul Kadir was proven to have committed a criminal act of fraud. This is in accordance with the first alternative indictment by the public prosecutor due to the fulfillment of the element of fraud as referred to in Article 378.